Resultado fiscal estrutural: Um passo para a institucionalizaç\~ao de políticas anticíclicas no Brasil - Sérgio Wulff Gobetti; Raphael Rocha Gouvêa; Bernardo Patta Schettini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This paper estimates the primary structural budget balance (eliminating the effects due to cyclical fluctuations in GDP and oil price) for the central government and public administrations from 1997 to the second quarter of 2010. Some adjustments were made on the IMF methodology to account for singularities of the Brazilian case. These procedures demand estimates for the trend GDP, as well as elasticities of the main components of the government budget with respect to GDP and oil price. To obtain a smoothed series for GDP (and oil price), we used the Hodrick-Prescott filter. To estimate the elasticities, we applied various techniques allowing for nonlinearities in the data. We did not perform any adjustment for the expenditure series, given they seem to have exhibited a procyclical behavior. In a nutshell, the statistics allow us to distinguish two big cycles of fiscal policy in the period under analysis: one of fiscal contraction, which was extended until the end of 2005; and another of fiscal expansion, from 2006 on. The calculations performed with the most conservative elasticities also suggest that the fiscal expansion in 2009, during the crises, was of approximately, 7% of GDP in the federal level and 0,2-0,4% of GDP in the public administrations as a whole. The partial results for 2010 indicate an impulse in the public administrations expenditure (from 0,2-0,4 to 0,4-0,8% of GDP). Nonetheless, the regional governments seemed now to have played a more central role, probably due to the proximity of the elections.
Keywords: E32; E62; H60; 330; Antizyklische Finanzpolitik; Brasilien